Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A.; Molinas, M.; GUTIÉRREZ, E. (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A.; Bertoni, G.; Molinas, M.; Oliva, M.; Domínguez-Planella, A. (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber

El crecimiento radial del alcornoque en cinco parcelas de alcornocal de Girona - Caritat, A.; Molinas, M.; Oliva, M. (Scientia gerundensis, 1992)
Tree rings of Quercus suber L. are porous and difficult to read because of the irregular growth rhythm. Radial growth has been measured in five experimental plots situated in the region of Girona (Catalonia, NE Spain). Cores of ten standard trees of each plot were extracted using a Pressler borer. In three plots woody disks from standard trees were also obtained. Tree rings were examinated under binocularlens. The CATRAS computer program (Anio1,1983 ) was used to find statistical parameters. Tree rings have an average width changing from 1,21 to 3,74 mm, while average standard deviation varies from 0,24 to 1,88 mm. and autocorrelation from 0,008 to 0.894 . These values are similar to those found in other Mediterranean Quercus, like Q. ilex L. The studied cork-oak plots ,with diametrical classes between 5 and 57 cm, show regular growth characteristic of young forest. The St. Hilari plot has the maturest trees, (diametrical classes from 24 to 57 cm) and this fact was reflectedin thegrowthcurve. Suddengrowthincreases are attributed to forestry management measures like clearing or selective cutting down. The effects of periodic cork extractions could no be clearly appreciated in this study.
Keywords: cork-oak; Mediterranean sclerophylls; Quercus suber L.; Radial growth; wood rings